A quantitative outlook of competitive strategy development in the oil market of China - Li Zhendong; Galymzhan Beisembayev (European Research Materials, 2024)
As many countries set ambitious "carbon peak, carbon neutral" goals, various industries are now actively engaging in carbon reduction initiatives. While some countries are at different stages in achieving carbon neutrality, especially developing nations requiring a gradual transition, the demand for fuel-powered vehicles remains robust. Consequently, fuel continues to dominate the energy landscape in the short term, resulting in intense competition within the gas station industry [1]. However, with the rapid advancement of new energy technologies and the exponential growth of electric vehicles (EVs), the era of fuel vehicles is inevitably waning. Hence, the oil industry faces an urgent imperative for business transformation. Each oil company maintains different resources and competitive advantages. How to improve now and future strengths and successfully transform into a carbon-neutral world is worth deep thinking about for each company. The purpose of this study is to assess the competitive strategy for oil company whose main business is gas station operation, by analyzing the environment and current strategy of the company.